Tadabbur Al-Qur’an Daring: Studi Netnografi tentang Aktivitas dan Motif Anggota Komunitas Jurnal Al-Qur’an Indonesia - Moh. Muhyiddin; Fauhatul Fawwazah (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The practice of Qur’anic tadabbur has developed dynamically along with the expansion of digital religious engagement and social media-based learning communities. The Jurnal Al-Qur’an Indonesia community represents a digital platform that facilitates online Qur’anic reflection through Qur’an journaling, Instagram, Telegram, Zoom, and related learning resources. This study aims to analyze the forms of online Qur’anic tadabbur activities and the motives of community members in participating in these activities. This research employed a qualitative netnographic design, with data collected from Telegram and Instagram interactions, posts, stories, Padlet materials, video recordings, screenshots of tadabbur outcomes, and supporting documents. The data were analyzed through data reduction, data display, interpretation, and conclusion drawing. The findings show that online Qur’anic tadabbur in this community is organized through weekly tadabbur, thematic tadabbur, Qur’an journaling challenges, and intensive classes or workshops. The Qur’an journaling process includes preparation, verse selection, understanding the verse, reflection, journaling, and digitization of the reflection results. The motives of members are grouped into information motives, social interaction and integration motives, and entertainment or emotional healing motives. This study contributes to the development of digital Islamic studies by showing that online Qur’anic tadabbur functions not only as a religious learning practice, but also as a mediated space for spiritual reflection, community support, and affective engagement with the Qur’an.